Cdc42‐dependent F‐actin dynamics drive structuration of the demarcation membrane system in megakaryocytes. (21st April 2016) - Antkowiak, A.; Viaud, J.; Severin, S.; Zanoun, M.; Ceccato, L.; Chicanne, G.; Strassel, C.; Eckly, A.; Leon, C.; Gachet, C.; Payrastre, B.; Gaits‐Iacovoni, F.
Abstract : Essentials Information about the formation of the demarcation membrane system (DMS) is still lacking. We investigated the role of the cytoskeleton in DMS structuration in megakaryocytes. Cdc42/Pak‐dependent F‐actin remodeling regulates DMS organization for proper megakaryopoiesis. These data highlight the mandatory role of F‐actin in platelet biogenesis. Summary: Background: Blood platelet biogenesis results from the maturation of megakaryocytes (MKs), which involves the development of a complex demarcation membrane system (DMS). Therefore, MK differentiation is an attractive model for studying membrane remodeling. Objectives: We sought to investigate the mechanism of DMS structuration in relationship to the cytoskeleton. Results: Using three‐dimensional (3D) confocal imaging, we have identified consecutive stages of DMS organization that rely on F‐actin dynamics to polarize membranes and nuclei territories. Interestingly, microtubules are not involved in this process. We found that the mechanism underlying F‐actin‐dependent DMS formation required the activation of the guanosine triphosphate hydrolase Cdc42 and its p21‐activated kinase effectors (Pak1/2/3). Förster resonance energy transfer demonstrated that active Cdc42 was associated with endomembrane dynamics throughout terminal maturation. Inhibition of Cdc42 or Pak1/2/3 severely destructured the DMS and blocked proplatelet formation. Even though this process does not require containment within the hematopoietic niche, because DMS structuration was observed upon thrombopoietin‐treatment in suspension, integrin outside‐in signaling was required for Pak activation and probably resulted from secretion of extracellular matrix by MKs. Conclusions: These data indicate a functional link, mandatory for MK differentiation, between actin dynamics, regulated by Cdc42/Pak1/2/3, and DMS maturation.